Gray Whale Distribution and Catch by Alaskan Eskimos: A Replacement for the Bowhead Whale? - Marquette, William M.; Braham, Howard W. (ARCTIC, 1982)
The catch of gray whales, Eschrichtius robustus, by Alaskan Eskimos from 1925 to 1980 has been documented to the extent possible by a search of the literature and personal communications with knowledgeable sources. During the period 1950-1980, 47 gray whales were landed by hunters at 12 villages. During this same period, 505 bowhead whales, Balaena mysticetus, were landed at nine coastal whaling villages. Alaskan Eskimos traditionally have been bowhead whalers, principally because of the predictive nature of the bowheads' migration. Gray whaling has never been an important subsistence activity. Because the bowhead population is thought to be depleted, gray whales have been suggested as a possible substitute for subsistence. The distribution of gray whales in Alaskan coastal waters is such that reliable annual whaling for this species is possible only at villages on the shores of the northern Bering Sea; it is unlikely for villages north of Bering Strait to Cape Lisburne, and more unlikely for villages north of Cape Lisburne and east of Point Barrow. Based on cultural and biological grounds, substituting gray whales for bowheads does not appear to be a reliable alternative for the residents of four to six of the nine Eskimo villages that currently participate in bowhead whaling.Key words: gray whale, Eschrichitus robustus; bowhead whale, Balaena mysticetus; Eskimos; subsistence whaling; Alaska Mots clés: baleine grise de Californie, Eschrichtius robustus; balaine boréale, Balaena mysticetus; Esquimaux, chasse à la baleine comme activité de subsistance, Alaska